A Consonant/Vowel Asymmetry in Word-form Processing: Evidence in Childhood and in Adulthood. (June 2014) - Havy, Mélanie; Serres, Josette; Nazzi, Thierry
In the literature, consonants have been proposed to be more important than vowels in lexical activation and access processes. However, despite a large body of evidence in the infant and adult literature, a recent study revealed a disappearance of the bias in newly learned words over the preschool years (Havy, Bertoncini, & Nazzi, 2011). As a first explanation of this developmental change, one might consider that the bias initially applies to all lexical processes to progressively narrow down its influence to specific cognitive and lexical mechanisms. Alternatively, the task used to address this question in Havy et al. (2011) might not have been sensitive enough to capture the bias in new-word learning from a certain age. The aim of the present study was to evaluate the extent to which the pattern observed over this period of development resulted from a lack of sensitivity of the task or from a real disappearance of the consonant bias during word learning. To address this issue, we designed two experiments evaluating the strength of the consonant bias during word learning in preschoolers and adults in 'congruent' versus 'incongruent' situations. Both experiments tested the recognition of a target object among two objects with similar names. In the congruent situation, the proposed target corresponded to one of the items presented. In the incongruent situation, the target differed from one of the items by a consonant and from the other by a vowel. Both experiments revealed the existence of a consonant bias in childhood and in adulthood. There was no difference between onset and coda processing in the congruent situation, but there was a slight advantage in adulthood for the first congruent information perceived in the incongruent situation.